Using Genetics and Morphology to Examine Species Diversity of Old World Bats: Report of a Recent Collection from Malaysia - Anwarali, F. A.; Vicki J., Swier; Solari, Sergio; Peter A., Larsen; Ketol, Besar; Marni, Wahap; Ellagupillay, Sivanathan; Lakim, Maklarin; Abdullah, M.T; Robert J., Baker (Museum of Texas Tech University, 2008)
A three-week field survey was conducted to sample bat species diversity in Malaysia. The survey sampled five localities during August 2006, including one in Peninsular Malaysia and four in Borneo. A total of 259 specimens representing at least 50 species were recorded. Three sampling nights were spent at each locality; four harp traps and 15 mist nets were set most nights. The highest species diversity was recorded in Mount Penrisen (Borneo) with 27 species, whereas the lowest diversity was at Monggis Sub Station and Bako National Park (Borneo) with 13 species each. We added four new geographic records for Sarawak, Malaysian Borneo: Arielulus cuprosus, Hesperoptenus tomesi, Kerivoula lenis, and Myotis adversus; and the second record of Hipposideros doriae in Sarawak. Other findings included a colony of earwigs collected from an Eonycteris major and the documentation of highly developed facial glands on male Hipposideros ater and H. galeritus. Species were identified using traditional skin and skull characteristics as well as mitochondrial cytochrome-b gene sequences that were compared to existing GenBank records. This multifaceted approach, using genetic and morphological identifications, has provided greater resolution to species identification as well as a better understanding of the diversification of Old World Bats from Malaysia. Although in most cases genetic data validated the present taxonomy, there were still a number of cases of cryptic species suggesting an underestimation of the actual biodiversity. This study has demonstrated the value of genetic data in providing an independent test for species boundaries among the 50 species of bats collected (about 40% of the known Malaysian bat fauna).